La femme et le pantin. Roman Espagnol - Louÿs, Pierre 1870-1925; Mondor, Henri 1885-1962; Galanis, Démétrius Emmanuel 1882-1966 (Paris Sauret, 1958)
During the carnival in Seville, the Frenchman André Stévenol meets and falls under the spell of Concepción 'Conchita' Pérez, a young Andalusian woman. His friend, don Mateo Diaz warns him off by describing his own history with the woman – a history of being repeatedly attracted and then rebuffed by her. Conchita continually flirted with other men to torture don Mateo. On each occasion he was made to feel guilty for his jealous thoughts and actions towards her, until he realised finally that he had been her puppet for fourteen months and in an explosion of passion he beat her. She then astonished him by declaring the violence a sign of the strength of his love and came to his bed. She was a virgin. Although the two then started living together, she continued her flirtatious behaviour towards other men and simultaneously became very possessive. Don Mateo left the country and travelled for a year to escape her.The novel has a short epilogue, described as the moral of the piece. The Frenchman accidentally meets Conchita again, and they spend the night together. The next morning, as Conchita packs her bags for Paris, a note is received from don Mateo asking to be taken back into Conchita's good graces
Pierre Louÿs (1870-1925) was a French poet and writer, most renowned for lesbian and classical themes in some of his writings. He is known as a writer who sought to "express pagan sensuality with stylistic perfection". He was made first a Chevalier and then an Officer of the Légion d'honneur for his contributions to French literature.
Originally published in 1898
Suivi de "Poèmes"
Keywords: 20th Century (1901-2000); Literature; Novel; Poetry; Paris (France)